2023
DOI: 10.1051/0004-6361/202346795
|View full text |Cite
|
Sign up to set email alerts
|

HYPerluminous quasars at the Epoch of ReionizatION (HYPERION): A new regime for the X-ray nuclear properties of the first quasars

L. Zappacosta,
E. Piconcelli,
F. Fiore
et al.

Abstract: The existence of luminous quasars (QSOs) at the epoch of reionization (EoR; i.e., z > 6) powered by well-grown supermassive black holes (SMBHs) with masses ≳109 M⊙ challenges models of early SMBH formation and growth. To shed light on the nature of these sources, we started a multiwavelength program based on a sample of 18 HYPerluminous quasars at the Epoch of ReionizatION (HYPERION). These are the luminous QSOs whose SMBHs must have had the most rapid mass growth during the first gigayear of the Universe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…Besides the possibilities discussed above, the lack of X-ray detections for high-z AGNs might be also explained by the possible evolution of the X-ray spectral shape. For example, Zappacosta et al (2023) found the X-ray spectra of 10 quasars at z > 9 have a steeper average photon index (Γ ≈ 2.4 ± 0.1) than classical values (Γ ∼ 1.8-2). For such systems, even their X-ray luminosity can be high; their redshifted spectrum at the commonly observed X-ray energy band could be a factor up to 4-5 times fainter than standard AGNs, which can greatly reduce the chance of detection.…”
Section: Miri Agns Without X-ray Detectionsmentioning
confidence: 99%
“…Besides the possibilities discussed above, the lack of X-ray detections for high-z AGNs might be also explained by the possible evolution of the X-ray spectral shape. For example, Zappacosta et al (2023) found the X-ray spectra of 10 quasars at z > 9 have a steeper average photon index (Γ ≈ 2.4 ± 0.1) than classical values (Γ ∼ 1.8-2). For such systems, even their X-ray luminosity can be high; their redshifted spectrum at the commonly observed X-ray energy band could be a factor up to 4-5 times fainter than standard AGNs, which can greatly reduce the chance of detection.…”
Section: Miri Agns Without X-ray Detectionsmentioning
confidence: 99%
“…where the specific comoving emissivity at 2 keV, ò 2 (z), is related to the AGN emissivity at the Lyman limit by (1) a "high-background" case with α OX = −1.35 (as in Model I) and α X = −0.9 (the canonical value for X-ray-selected AGNs; see, e.g., Merloni et al 2014); (2) a "low-background" case with α OX = −1.8 (as in Model II) and α X = −1.4, the steep value that is characteristic of luminous, z > 6 quasars (Zappacosta et al 2023) and of close-to-Eddington sources (Tortosa et al 2023). As shown in Figure 5, even for the high-background extreme parameters we obtain EI E ; 10 −9 erg s −1 cm −2 sr −1 at 2 keV, a contribution that would not saturate the unresolved XRB measured by Moretti et al (2012).…”
Section: Integrated Optical Depth To Reionizationmentioning
confidence: 99%